Crossing a narrow-in-altitude turbulent auroral acceleration region - R. Pottelette (Nonlinear Processes in Geophysics, 2004)
We report on the in situ identification of a narrow electrostatic acceleration layer (electrostatic shock) containing intense plasma turbulence in the upward current region, and its effect on auroral particles. Wave turbulence recorded in the center of the layer differs in character from that recorded above and beneath. It is concluded that the shock is sustained by different nonlinear waves which, at each level, act on the particles in such a way to produce a net upward directed electric field. The main power is in the ion acoustic range. We point out that anomalous resistivities are incapable of locally generating the observed parallel potential drop.